A novel approach for restoration of hemisected mandibular first molar with immediately loaded single piece BCS implant: A case report - Mahender Singh; Ranmeet Batra; Debdutta Das; Shweta Verma; Munish Goel (Elsevier, 2017)
Mandibular first molars are the major standpoint for occlusion, and also have a wide peri-cemental area. Under specific conditions, hemisection of the tooth is indicated after an endodontic treatment. The following case report presents the hemisection of grossly carious, endodontically treated mandibular first molar, in a 23 year old female, followed by replacement of the mesial root with a single piece immediate loaded BCS (Bi-Cortical Screw) implant and a single unit porcelain fused to metal crown for the prosthetic rehabilitation of the remaining tooth structure, with the BCS implant providing strength and support to the weakened tooth structure. This procedure is an innovation in prosthetic rehabilitation of tooth structure left after hemisection and enhances the predictability of success rate of hemisection.